Are the Agro-Ecosystems Sustainable? Measurement and Evaluation: A Case Study of Sichuan Province, China - Dai, Xiaowen; Chen, Yi; Wu, Xin; He, Yanqiu; Wang, Fang (Frontiers in Environmental Science, 2022)
In recent years, with the frequent occurrence of global climate problems, China has paid great attention to sustainable development and ecological environment governance. Sichuan Province is a significant grain production and a reserve base in western China, and its sustainable development in agriculture is an important foundation for the healthy development of the regional agricultural economy and food security. In this study, we divided the agricultural production land in Sichuan into cultivated land, water area, grassland, and forest land. We used the ecological footprint method to investigate the ecological footprint and the carrying capacity of agriculture in Sichuan comprehensively. We conclude that 1) generally, the overall agricultural ecosystem in Sichuan has been in a state of ecological surplus for the past 20 y, and the environmental pressure is gradually decreasing. However, the development within the ecosystem is uneven. 2) In terms of subdivision, the cultivated land, forest land, and water area in Sichuan have always been in a state of ecological surplus, but the grassland is in an ecological deficit state. In terms of the trend, the ecological status of cultivated land has declined significantly, while the forest land has gradually improved, and the water area is relatively stable. Yet, the deficit of grassland is still severe. 3) Forest land is considered the most sustainable type and has a high resource utilization rate all the time, followed by water area, cultivated land, and grassland, when measured by ecological indicators. At the same time, in terms of the coordination between economy and ecology, all lands have been improved.